Single‐cell TCR repertoire analysis reveals highly polyclonal composition of human intraepithelial CD8+ αβ T lymphocytes in untreated celiac disease. Issue 6 (26th February 2021) - Eggesbø, Linn M.; Risnes, Louise F.; Neumann, Ralf S.; Lundin, Knut E. A.; Christophersen, Asbjørn; Sollid, Ludvig M.
Abstract : We compared the αβ T‐cell receptor repertoires of CD8 + αβ intraepithelial lymphocytes from celiac disease patients and healthy subjects by single‐cell sequencing. We demonstrate that the repertoires of untreated celiac disease patients were more polyclonal and more diverse than what was observed in both treated patients and healthy subjects.